FRACTIONATION OF FATTY ACID OMEGA 3, 6 AND 9 FROM SNAIL (Achatina fulica) USING COLOUM CHROMATOGRAPHY - Winarto Haryadi; Sugeng Triono (Indonesian Journal of Chemistry, 2006)
The extraction of fat from snail has been carried out by Soxhlet extractor with petroleum ether solvent. Fatty product from extraction was transesterificated in BF3/methanol solvent for an hour by reflux procedure, then extracted by n-hexane to produce methyl ester fatty acid. Free water fatty acid methyl ester was analyzed by Gas Chromatography-Mass spectrometer (GC-MS). Fatty acid ester was separated from its fractions use column chromatography in n-hexane, n-hexane:dietil eter (2:1 v/v), dietil eter, aseton, ethanol and methanol. This fractions wer also analized by GC-MS. From GC-MS data sheet can be obtained 5 fractions which details are; fraction 1 contains omega 3: 27.54 %, omega 6: 15.40 % and omega 9: 6.77 %. Fraction 2 contains omega 3: 3.08 %, omega 6: 15.62 % and omega 9: 10.72 %. Fraction 3 contains omega 6: 3.57 %, omega 9: 7.02 % and none omega 3 inside it. Omega 3, 6 and 9 can't be identification in fraction 4 and 5.